Protection of Land Ownership Rights in Cases of Unlawful Acts - Najmi, Maulida Syahrin; Djajaputra, Gunawan (Trunojoyo Madura University, 2025)
Land issues, especially those related to the control of cultivated land, are still a complex legal issue in Indonesia. Cultivated land is land managed by another party without certainty of rights, and has not been explicitly regulated in the Basic Agrarian Law Number 5 of 1960. Unlawful acts as regulated in Article 1365 of the Civil Code are the legal basis for demanding compensation for illegal acts such as control of land without permission. Although the legal basis for protecting land rights has been regulated in the Civil Code and the 1945 Constitution, in practice, legal owners often face administrative, socio-cultural obstacles, and weak law enforcement. This study uses a literature study method with a qualitative approach to examine these issues and alternative dispute resolution through civil law, summons, mediation, and arbitration. The complexity of overlapping national law, customary law, and regional regulations exacerbates legal uncertainty so that land rights protection is less than optimal.